COVID-19 lessons for crisis management and recovery in the food service industry in Indonesia - Subakti, Agung Gita; Omar, Hamimi; Mohamed, Ahmad Edwin Bin (Edelweiss Applied Science and Technology, 2025)
This study aims to examine the crisis management strategies employed by local restaurants in Indonesia during and after the COVID-19 pandemic, and to evaluate their effectiveness and applicability for future crises. Using Faulkner’s Six Stages of Crisis Management framework, the research identifies five major themes: financial resilience, operational flexibility and service adaptation, digital transformation and customer engagement, long-term learning and strategic preparedness, and reactive crisis response. A qualitative, exploratory multiple-case study design was adopted, with data collected through semi-structured interviews involving restaurant owners and managers in Jakarta. Thematic analysis was conducted using NVivo 12, supported by member checking and peer review to ensure credibility. Findings show that Indonesian restaurant operators utilized both proactive and reactive strategies, such as financial restructuring, digitalization, and operational adjustments. The study also uncovers challenges related to government regulations and shifts in consumer behavior. The research concludes that adaptive business models and strategic preparedness are essential for resilience. Practical implications suggest that both policymakers and hospitality practitioners should integrate adaptive frameworks and digital tools to better prepare for future disruptions. This study contributes to the empirical validation of Faulkner’s model in the context of real-world crises.